PENGARUH BRAND IMAGE, DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK SIGNATURE DI COFFEE SHOP GEMATI KOTA SURAKARTA - Farrel Putra Artantyo; M. Farid Wajdi (JURNAL LENTERA BISNIS, 2025)
The objective of this research is to examine the impact of brand image, digital marketing, and electronic word of mouth (e-WOM) on consumers’ purchasing decisions regarding signature products offered by Gemati Coffee Shop in Surakarta. This investigation employed a non-probability sampling strategy, specifically utilizing purposive sampling to select participants. Data were gathered through a structured questionnaire using a Likert scale to measure responses. The target population comprised individuals from the general public who expressed an intention to purchase the coffee shop's signature products, with a total sample size of 100 respondents. Empirical findings from the study reveal that both brand image and e-WOM exert a statistically significant and positive influence on purchasing decisions. Conversely, digital marketing was found to have no significant effect on consumer choices. These results contribute to the understanding of key determinants shaping purchasing behaviors in the context of local specialty coffee establishments, with a particular focus on Gemati Surakarta. The lack of a notable impact from digital marketing presents a noteworthy contradiction to prevailing assumptions regarding its effectiveness, suggesting the need for more nuanced and consumer-oriented marketing approaches. This insight emphasizes the pivotal role of brand perception and consumer-driven communication in formulating successful promotional strategies.